Institutional Profile: McGowan Institute for Regenerative Medicine. (January 2010) - Russell, Alan
The McGowan Institute was launched in 2001 as a joint program between the University of Pittsburgh and the University of Pittsburgh Medical Center. Building from the success of the McGowan Center for Artificial Organs, the McGowan Institute employs three main pillars of research from which to accelerate research and development in regenerative medicine. It is the coalescence of these main foci –– tissue engineering and biomaterials, cellular therapy, and medical devices and artificial organs –– which enable McGowan to thrive in such a competitive field.